2016
DOI: 10.1371/journal.pone.0154576
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells in Small Cell Lung Cancer Cell Line H446: Higher Dependency on Oxidative Phosphorylation and Mitochondrial Substrate-Level Phosphorylation than Non-Stem Cancer Cells

Abstract: Recently, targeting cancer stem cells (CSCs) metabolism is becoming a promising therapeutic approach to improve cancer treatment outcomes. However, knowledge of the metabolic state of CSCs in small cell lung cancer is still lacking. In this study, we found that CSCs had significantly lower oxygen consumption rate and extracellular acidification rate than non-stem cancer cells. Meanwhile, this subpopulation of cells consumed less glucose, produced less lactate and maintained lower ATP levels. We also revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…In our studies, we confirmed the relationship between uPAR and metabolism, which has already been partially observed by Gao C et al [42], using FACS sorted cells for uPAR from a small cell lung cancer cell line. We validated our previous work proving that uPAR overexpression plays a central role in the Warburg-like metabolism of cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…In our studies, we confirmed the relationship between uPAR and metabolism, which has already been partially observed by Gao C et al [42], using FACS sorted cells for uPAR from a small cell lung cancer cell line. We validated our previous work proving that uPAR overexpression plays a central role in the Warburg-like metabolism of cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…3a). Besides, the DNA replication pathway19 commonly found by PD and SAM, the other 13 significant pathways are mainly associated with lung cancer, including pentose phosphate pathway20, oxidative phosphorylation921, cysteine and methionine metabolism22, glutathione metabolism101112, biosynthesis of amino acids23, ribosome24, proteasome13, protein processing in endoplasmic reticulum2526, phagosome27 and TNF signaling pathway28. These conservative pathways included many DE genes highly expressed in both cancer and normal tissues, which tended to be missed by SAM.…”
Section: Resultsmentioning
confidence: 99%
“…We recently proposed that most of the ATP synthesized in tumor cells would come from mitochondrial substrate level phosphorylation (mSLP) at the succinate ligase reaction (46). Evidence showing that mSLP can compensate for OxPhos deficiency in cancer is emerging (57)(58)(59)(60). mSLP could also compensate for minimal energy production through glycolysis due to the predominance of the glycolytic pyruvate kinase M2 (PKM2) isoform, which produces less ATP than the PKM1 isoform (61).…”
Section: Glutaminolysismentioning
confidence: 99%